Alona pectinata (Crustacea: Anomopoda; Chydoridae), a new freshwater cladoceran from Southeast Mexico - Elías-Gutiérrez, M.; Suárez-Morales, E. (Revista de Biología Tropical, 1999)
A new species of the chydorid cladoceran genus Alona is described herein from parthenogenetic females. The material was collected from several fresh water lagoons and pools in the southem portion of the Yucatan Peninsula, Mexico at an altitude less than 100m above sea level. The new species can be distinguished from other species of Alona by the combination of several features: a well-developed armature of the antennae, postabdomen, and postabdominal claw, the outer distal lobe ofthe first thoracic limb bears two pecten-like setae. and the exopod of thoracic limb III has only five setae. This new taxon is related to other species of Alona described from South America and the Old continent.